The Fetal Medicine Foundation (FMF) Germany after 20 years: quality assurance of ultrasound examinations during first trimester screening : editorial = 20 Jahre Fetal Medicine Foundation (FMF) Deutschland : ein Beitrag zur Qualitätssicherung der Ultraschalluntersuchung beim Ersttrimester-Screening - Merz, Eberhard; Thode, Ch; Hackelöer, B. J.; Eiben, B.; Faber, R.; Tercanli, S.; Huda, E.; Wellek, Stefan (Ultraschall in der Medizin, 2022)
Thieme E-Books & E-Journals